Subcellular insight into cholesterol-mediated proliferation of the tick cell line - Kropáčková, Sára (Jihočeská univerzita, 2022)
Arthropods, including ticks, are not able to synthetise cholesterol de novo. However, cholesterol is an essential component of their cell membranes and serves as a precursor for the synthesis of steroid hormones. In this thesis, I looked at the biological function of exogenous cholesterol on the tick Ixodes ricinus cell line IRE/CTVM19. I verified the need for cholesterol supplementation in the growth medium for proper cell proliferation. Cellular proliferation was stimulated by cholesterol and not by other sterols (ergosterol, sitosterol). We further explored the two assumed aforementioned cholesterol cellular roles, but also investigated the role of cholesterol as a signal molecule: The effect of cholesterol sensing is described on the tick cell level, as well as on the level of the whole organism, using the ex vivo feeding system of ticks. This work provides novel insights into the cholesterol biology of ticks and tick cells, increasing our understanding of tick-host blood molecules' interaction.
Subcellular insight into cholesterol-mediated proliferation of the tick cell line
Keywords: tick; cholesterol; tick cell line; IRE/CTVM19; Hedgehog signalling pathway; tick; cholesterol; tick cell line; IRE/CTVM19; Hedgehog signalling pathway